2005
DOI: 10.1038/sj.ejcn.1602098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous β-galactosidase in patients with lactose malabsorption and intolerance: a crossover double-blind placebo-controlled study

Abstract: Objective: To evaluate the efficacy of the addition to milk, 5 min and 10 h before its consumption, of a lactase obtained from Kluyveromyces lactis in lactose malabsorbers with intolerance. Design: Double-blind, placebo-controlled, crossover study. Setting: University Hospital. Subjects: In total, 11 male and 19 female (aged from 18 to 65 y, mean age 43.3 y) lactose malabsorbers with intolerance participated. Interventions: Each patient underwent three H 2 breath tests, in a random order. We used 400 ml of cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 20 publications
(19 reference statements)
2
42
0
Order By: Relevance
“…Numerous studies have shown that individuals with hypolactasia could tolerate fermented dairy products better than an equivalent quantity in milk (Hertzler & Clancy, 2003;Montalto et al, 2005;Vesa et al, 1996). Various explanations have been suggested in order to clarify this phenomenon.…”
Section: Alleviation Of Lactose Intolerancementioning
confidence: 96%
“…Numerous studies have shown that individuals with hypolactasia could tolerate fermented dairy products better than an equivalent quantity in milk (Hertzler & Clancy, 2003;Montalto et al, 2005;Vesa et al, 1996). Various explanations have been suggested in order to clarify this phenomenon.…”
Section: Alleviation Of Lactose Intolerancementioning
confidence: 96%
“…Secondly, a precise method exists for the determination of the substrate/product concentration of β-galactosidase, and consequently, the amount of enzyme. The method is well standardized since the quantitative estimation of lactose in dairy products is a common procedure due to the large number of people with lactose intolerance (22)(23)(24). Thirdly, to prove that the surface-modified powder remains dry and no degradation product appeared as an enzymatic reaction requires water.…”
Section: Protein Mist Coatingmentioning
confidence: 99%
“…However, more data regarding the efficacy of this microbial exogenous enzyme are needed [37]. Other evidence suggested that efficacy of exogenous lactase was obtained from Kluyveromyces lactis , Aspergillus oryzae , or Kluyveromyces lactis [38, 39]. Another strategy involves probiotics that could shape gut microbiota composition.…”
Section: Management Of Lactose Intolerance and Nutritional Issuesmentioning
confidence: 99%